2016
DOI: 10.1111/ffe.12382
|View full text |Cite
|
Sign up to set email alerts
|

Extending structural health monitoring concepts for bone healing assessment

Abstract: A B S T R A C T A series of experimental investigations are performed to show the potential of integrating sensing elements into an external fixation for healing assessment of a fracture femur. This investigation is supported by finite element analyses that highlight the fundamental structural dynamics, which enable a stiffness-based healing assessment methodology. A saw-bone femur externally fixated with a Hoffman II will be subjected to an artificial fracture. The healing of the fractured femur is simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…The B&K Photon + has an internal analogue filter and a 160 dB/octave line-phase digital filter to present aliasing and phase distortion. Unlike previous works, 5,16 the forcing was applied without the use of an instrumented forcing device. Instead, the two-sensor system measures the dynamic response of the fixated femur and along with a statistical assessment of the validity of the data acquired.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B&K Photon + has an internal analogue filter and a 160 dB/octave line-phase digital filter to present aliasing and phase distortion. Unlike previous works, 5,16 the forcing was applied without the use of an instrumented forcing device. Instead, the two-sensor system measures the dynamic response of the fixated femur and along with a statistical assessment of the validity of the data acquired.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Furthermore, these assessments are correlated to clinical findings that involve patients' verbal description on weight-bearing pain to associate bone healing which is often inaccurate in determining the state of healing and union of the fracture. 5 Therefore, there is currently no robust or reliable method to adequately quantify the load sharing between the internal fixation and bone during different stages of healing.…”
Section: Introductionmentioning
confidence: 99%
“…In the work funded by the United States Office of Naval Research (ONR), Ong et al [44] indicated that there is a strong dependence of dynamic response on structural properties of a given construct. In the recent research funded by ONR, Ong et al [44,45] proposed a concept of integrating the sensing elements into external fixation to monitor fracture healing remotely. In their research [44], the potential of locating sensors on the external fixation and the appropriate frequency range were conceptualised using a series finite element analysis.…”
Section: Vibration Response With External Fixationmentioning
confidence: 99%
“…In the recent research funded by ONR, Ong et al [44,45] proposed a concept of integrating the sensing elements into external fixation to monitor fracture healing remotely. In their research [44], the potential of locating sensors on the external fixation and the appropriate frequency range were conceptualised using a series finite element analysis. This is then substantiated with a series of experimental study.…”
Section: Vibration Response With External Fixationmentioning
confidence: 99%
See 1 more Smart Citation